Структура переходного слоя и прочность соединения напеченных на стальную основу слоев из различных матричных материалов методом интенсивного электроспекания - Иванов, С.А.; Переяслов, В.П.; Майстренко, А.Л.; Ващенко, А.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
This paper presents the results of examinations on definition of linking strength of sintered on the steel mount by a method of intensive electrosintering at heightened pressure briquetted layers from different matrix materials designed for usage in rock-destroying and dressing instruments. Is shown, that due to saving of diamonds properties and high mechanical properties of matrix the designed instrument for dressing and drills for handling a natural rock has high indexes of endurance and productivity.